Wind farm connected to a grid using fuzzy logic controller based the unified power flow controller - Rabyi Tarik; Brouri Adil (Institute of Advanced Engineering and Science, 2022)
The doubly-fed induction generator (DFIG) based wind farm is widely used for extracting energy from the wind. When the wind farm is connected to the grid, generally it causes some perturbations. It can disturb the function of the grid and the installations connected to the grid. This impact concerns the load flow, voltage drops, and frequency fluctuations. To overcome those issues, the unified power flow controller (UPFC) is recommended. In this paper, we propose to study the impact of the integration of a wind farm on the power system. Presently, we propose an original contribution by using UPFC based on fuzzy logic controllers (FLC). Finally, simulation and experimental results using MATLAB/Simulink are proposed to show the effectiveness of this solution.